1984
DOI: 10.1159/000249653
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Infection of the Ear

Abstract: Fungal infections of the auditory canal and middle ear are usually left unnoticed and regarded as a harmless saprophytic growth. However, these infections may become clinically significant in immunocompromised patients or patients undergoing long-term antibiotic treatment. This is demonstrated by characteristic case reports and confirmed by light and electron microscopic findings. Moreover, studies on animals with experimentally induced fungal infections have furnished evidence for the risk of the infection’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…The first hypothesis is the erosion of the bony wall by the fungus itself. Destruction of the bones including ossicles and bony walls of the mastoid cavity leading to semicircular canal fistula has been reported [13], and erosion of the ossicles was confirmed by an experimental study [3]. The second possibility is that the perilymph fistula was formed by the cooperation of fungal infection and cholesteatoma: the cholestetoma had caused the bony fistula, and then the massive granulations formed by the fungal infection detached from underneath the matrix covering the fistula, resulting in perilymph leakage.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…The first hypothesis is the erosion of the bony wall by the fungus itself. Destruction of the bones including ossicles and bony walls of the mastoid cavity leading to semicircular canal fistula has been reported [13], and erosion of the ossicles was confirmed by an experimental study [3]. The second possibility is that the perilymph fistula was formed by the cooperation of fungal infection and cholesteatoma: the cholestetoma had caused the bony fistula, and then the massive granulations formed by the fungal infection detached from underneath the matrix covering the fistula, resulting in perilymph leakage.…”
Section: Discussionmentioning
confidence: 91%
“…In the case of chronic otitis media, fungi can spread to the tympanic cavity, but it usually remains a harmless, saprophytic growth, which does not call for intensive clinical intervention [3]. Khanna et al [8] reported that a pure fungal culture was obtained in 9.0% of chronic suppurative otitis media cases, all of which responded to topical antifungal treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Even adenoid colonization followed by reflux otitis media has been proposed as a means of entry for fungal spores. 2 Fungi have been shown by Falser 6 to penetrate the oval and round window from the middle ear. In each of the cases presented, the host suffered from an immunocompromised state with likely colonization of the external ear preceding temporal bone involvement.…”
Section: Commentmentioning
confidence: 99%